The antiepileptic drug valproic acid and other medium-chain fatty acids acutely reduce phosphoinositide levels independently of inositol in Dictyostelium - Pishan Chang; Benoit Orabi; Rania M. Deranieh; Manik Dham; Oliver Hoeller; Jakob A. Shimshoni; Boris Yagen; Meir Bialer; Miriam L. Greenberg; Matthew C. Walker; Robin S. B. Williams (The Company of Biologists, 2012)
SUMMARY Valproic acid (VPA) is the most widely prescribed epilepsy treatment worldwide, but its mechanism of action remains unclear. Our previous work identified a previously unknown effect of VPA in reducing phosphoinositide production in the simple model Dictyostelium followed by the transfer of data to a mammalian synaptic release model. In our current study, we show that the reduction in phosphoinositide [PtdInsP (also known as PIP) and PtdInsP2 (also known as PIP2)] production caused by VPA is acute and dose dependent, and that this effect occurs independently of phosphatidylinositol 3-kinase (PI3K) activity, inositol recycling and inositol synthesis. In characterising the structural requirements for this effect, we also identify a family of medium-chain fatty acids that show increased efficacy compared with VPA. Within the group of active compounds is a little-studied group previously associated with seizure control, and analysis of two of these compounds (nonanoic acid and 4-methyloctanoic acid) shows around a threefold enhanced potency compared with VPA for protection in an in vitro acute rat seizure model. Together, our data show that VPA and a newly identified group of medium-chain fatty acids reduce phosphoinositide levels independently of inositol regulation, and suggest the reinvestigation of these compounds as treatments for epilepsy.